Complexidades Conceptuais e Inter-Relações: Alguns Contributos para a Definição do Ensino do Português como Língua Estrangeira - Osório, Paulo (2020)
This article has as main objective to share some reflexions about the complexities and the interrelations inherent to the area of Portuguese as a Foreign Language (PFL), while looking at its connections with conected areas, since it is characterized, from the outset, as an eminently interdisciplinary domain. Going over, albeit briefly, some of the main epistemological and terminological fluctuations (see Pinto, 2013) which have taken place in this scientific domain, it is worth noting the heterogeneity of the area, largely due to its variety and its open nature to non-linguistic factors, such as cultural, political and social issues, among others. This text, focusing mainly on PFL, with a focus on teaching contexts outside Portugal and other Portuguese speaking countries, is, therefore, a brief problematization solely intending to underline these epistemic fluctuations (cf. Pinto, 2009), as well as to highlight some of the many challenges facing the PFL teacher at all times.